Focusing on the ethnobotanical uses of plants in Mersin and Adana provinces (Turkey) - Ozturk Ersin; Everest Ayse (Journal of Ethnobiology and Ethnomedicine, 2005)
Abstract This paper presents the result of a study on the herbal drugs in the herbal markets in Mersin and Adana. The data were collected through direct interviews with herbalists and customers between 2002–2005 and the popular medicinal plants were investigated. A total of 107 species belonging to 56 families were investigated and the samples were listedwith their local and Latin names. The investigation includes cross-checking the disorders and their herbal cures and their recommended use stated by the local herbalists, by the parts used, and by the preparations. The cultivated species and their ethno botanical uses, are documented and extensive inventory is presented. As a result, we observed that these plants are used especially for intestinal digestive disorders of the gastrointestinal tract, (21.68%), respiratory tract system disorders (10.43%), heart-blood circulatory system disorders (8.48%), urinary tract system disorders (7.70%), skin disorders (6.48%) and others.